2017
DOI: 10.4103/jfmpc.jfmpc_359_16
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control targets in Sudanese adults with type 1 diabetes: A population-based study

Abstract: Background:Type 1 diabetes is a challenging metabolic disorder for health authorities in Sudan. The objective of this study was to assess the level of glycemic control and to determine the prevalence of dyslipidemia and complications among individuals with type 1 diabetes in Sudan.Materials and Methods:Individuals with type 1 diabetes, who were having the disease for at least 1 year, were invited to participate in this study. Data were collected from two diabetes centers, in the Capital Khartoum and Atbara Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Poor adherence to antidiabetic medications leads to inadequate blood glucose control, treatment failure, accelerated development of complications, and increased mortality. We have previously shown that 85% of Sudanese individuals with type 2 diabetes have poor diabetes control ( HbA1 c > 7 %) ( 26 ). This poor diabetes control can be attributed in part to poor diabetes medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Poor adherence to antidiabetic medications leads to inadequate blood glucose control, treatment failure, accelerated development of complications, and increased mortality. We have previously shown that 85% of Sudanese individuals with type 2 diabetes have poor diabetes control ( HbA1 c > 7 %) ( 26 ). This poor diabetes control can be attributed in part to poor diabetes medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 18 19 20 21 22 ] The high level of diabetes complications can be attributed to high prevalence of uncontrolled glycaemia. [ 23 24 ] Prediabetes is also a condition that associated with an increase in different comorbidities like hypertension, fatty liver polycystic ovary syndrome, hyperlipideamia, metabolic syndrome, an increase risk of cardiovascular disease, decrease in chromium and an increase in oral lesions. Importantly, diabetes was significantly associated with high hospital mortality with COVID-19, but prediabetes was not statistically associated with high hospital mortality[ 25 26 27 28 29 ]…”
Section: Discussionmentioning
confidence: 99%